From Guantanamo Bay to Abu Ghraib: Challenging and Reconciling the Universality of Human Rights - William W. Burke-White (حقوق بشر)
Over the past few years, two events have radically transformed American identity and global perceptions of America with respect to human rights. The first of these is the detention of “enemy combatants” at Guantanamo Bay and the second is the abuse of prisoners at Abu Ghraib prison in Iraq. This paper considers how Guantanamo and Abu Ghraib have altered the intellectual and popular perceptions of human rights in America and abroad. The paper argues that the very different reactions to these events in the US and abroad suggest a move toward a relativist view of human rights in the US, limited by necessity and legality, but a universalist approach to human rights abroad. Moving toward a common global understanding of necessity and legality is critical to the pursuit of universal human rights. The reactions to Guantanamo indicate a growing acceptance in the United States of a relative conception of human rights. In the winter and spring of 2003, United States military forces at Abu Ghraib prison committed a range of often gruesome violations of Iraqi prisoners.